Pengaruh Pemahaman dan Kesadaran Terhadap Kepatuhan Wajib Pajak dengan Sosialisasi Perpajakan Sebagai Variabel Moderasi (Studi Kasus pada Wajib Pajak Orang Pribadi Yang Terdaftar di Kantor Pelayanan Pajak (KPP) Pratama Tampan Pekanbaru) - Ocfani, Arin; marlina, evi; Fionsari, Dwi (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
This research aims to determine the effect of understanding and awareness on taxpayer compliance with tax socialization as a moderating variable. The research method used in this research is a quantitative method where the data collected in this research is primary data by distributing questionnaires directly to respondents. The population of this research is individual taxpayers registered at KPP Pratama Tampan. The total population of individual taxpayers registered with KPP Pratama Tampan in 2022 is 242,329 people. The analytical method used in this research is Moderated Regression Analysis (MRA) and processed using the SPSS version 26 program application. The results of this research show that partially understanding influences taxpayer compliance and awareness influences taxpayer compliance, tax socialization is unable to moderate understanding. and awareness of taxpayer compliance